MARKETING STRATEGY IN THE DIGITAL SPACE - Hushko, Serhii; Kulishov, Volodymyr; Puriy, Hanna; Hushko, Olena; Znotina, Daina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The aim of the research is to determine the preconditions for integration the Ukrainian digital market into the EU's Digital Single Market. The article is devoted to the definition of preconditions integration of Ukraine into a single digital market EU in accordance with the realities of the domestic market digital integration priorities. The article is identified trends in the development of Ukrainian market of digital technologies, comparison of individual indicators it development of appropriate indicators of the EU countries, revealed the degree of difference between these principles and trends, directions outlined measures to solve the problem "digitalization" Ukraine and creation of favorable conditions for cooperation with the European Union in the field of information and communications technology and future integration into the EU single digital market. It also identified high priority digital media channels and reasonable "gap" priorities of digital media distribution channels, due to the level of ICT use in countries. The paper analyzed Internet Stats and Facebook Usage in Europe and the necessity for priorities of the digital media space, depending on the selected region of the distribution at the stage of development of a marketing strategy. The research employed the following methods: monographic and descriptive, analysis and synthesis, comparative analysis, and statistical analysis.